OVERALL DESIGN OF WHEELED MOBILE SHIP LOADER AND SIMULATION ANALYSIS OF BOOM STRUCTURE - LIAO GuanFu; HU JiQuan (Jixie qiangdu, 2019)
Based on the design scheme and parameters of the wheeled mobile ship loader, the overall design of the ship loader was carried out. According to the structural characteristics of the boom of the wheeled mobile ship loader, the characteristic parameters were extracted, then the parametric model of the boom was established by using the APDL language of ANSYS, and the finite element analysis of the boom structure was carried out. Finally, the boom structure was optimized by using ANSYS software and optimization design technology. Under the condition of meeting the design requirements, the economy and reliability of the boom are realized. The results are as follows: because the lower articulation of the boom is close to the inlet and outlet, its force is also large, the head of the boom is equivalent to the cantilever beam and hangs the chute, the maximum stress of the boom appears at the lower articulation, and the maximum deformation occurs at the head of the boom; the total weight of the structure can be greatly reduced by adopting variable cross-section design of the boom structure.